Decision-Making Within Forensic Psychiatric Investigations: The Use of Various Information Sources by Different Expert Groups to Reach Conclusions on Legal Insanity - Lizel Göranson; Olof Svensson; Olof Svensson; Peter Andiné; Peter Andiné; Sara Bromander; Sara Bromander; Ann-Sophie Lindqvist Bagge; Ann-Sophie Lindqvist Bagge; Malin Hildebrand Karlén; Malin Hildebrand Karlén; Malin Hildebrand Karlén (Frontiers in Psychiatry, 2022)
BackgroundWhich type of information experts use to make decisions regarding legal insanity within forensic psychiatric investigations (FPI) is relatively unknown, both in general and when considering variations due to case context. It is important to explore this area to be able to counteract the effects of various kinds of cognitive bias.MethodThe aim was to explore whether FPI expert groups differed regarding case-specific as well as general use of information types required to make decisions on severe mental disorder (SMD). Three FPI case vignettes were presented to three professional groups involved in FPIs in Sweden (n = 41): forensic psychiatrists (n = 15), psychologists (n = 15), and social workers (n = 11). The participants reported which types of information they required to reach conclusions regarding SMD in each case. They also reported which types of information they had used within general FPI praxis during the previous year and the information types’ perceived usefulness.ResultsThe expert groups differed somewhat regarding what type of information they required for the cases (e.g., results from cognitive testing), but some information was required in all cases (e.g., client’s self-report). Regarding the preliminary assessment of SMD in the three cases, minor differences were found. Within the general FPI praxis, experts reported using several information types, while the general perceived usefulness of these sources varied.DiscussionThe professional groups relied partly on a “core” of information sources, but some case-specific adaptations were found. The professional groups’ inclination to suspect SMD also varied somewhat. This indicates a need to explore the potential consequences of these similarities and differences.